Reproducibility of Results for Cryopreservation of Different Variety Cuttings of Pomefruit Trees - Gorbunov, L. V. (Problems of Cryobiology and Cryomedicine, 2009)
Viable frozen-thawed samples of apple (Belyy Naliv, Teremok, Radost), pear (Velyka Litnya, Ulyublena Klapa, Vdala, Zelena Mliivska) were obtained. With dispersion analysis it has been established that the development probability of frozen-thawed plant cuttings depends on variety and cryopreservation method. Mean indices of viability for different apple varieties differ by 32% and pear by 86%. Maximal indices of cuttings’ viability are obtained after their temperature adaptation at -10°C during 14ч60 days, stepwise cooling of the samples with 0.1–0.5°C/hr rate down to -30°C (exposure 3–7 days), direct plunging into liquid nitrogen, storage from 1 to 30 days and thawing rate of 70°C/min.